The World Bank Legal Review : Law, Equity, and Development, Volume 2 - World Bank (Washington, DC: World Bank and Martinus Nijhoff, 2012)
The World Bank legal review: law, equity, and development, volume two, is a publication for policy makers and their advisers, attorneys, and other professionals engaged in the field of international development. It offers a combination of legal scholarship, lessons from experience, legal developments, and recent research on the many ways in which the application of law and the improvement of justice systems promote poverty reduction, economic development, and the rule of law. In keeping with the theme of the World Development Report 2006: equity and development, and following the success of the World Bank Group's legal forum on 'law, equity, and development' in December 2005, volume two of the World Bank legal review focuses on issues of equity and development. The volume draws together some of the key ideas of the Legal Forum, including articles by many of its distinguished participants, and explores the role of equity in the development process, highlighting how legal and regulatory frameworks and equitable justice systems can do much to level the playing field in the political, economic, and socio-cultural domains, as well as how they can reinforce existing inequalities.